Tinjauan Yuridis Mengenai Pertentangan Hukum Yang Hidup dalam Masyarakat dalam Pasal 2 pada Rancangan Kitab Undang-Undang Hukum Pidana dengan Asas Legalitas - Fadlilah, M Nabiel; fauziah, siti sa’adah; D.K, Andian Achya (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
The purpose of establishing the RKUHP is in line with the spirit of decolonization and particularization so that it incorporates elements of law that live in society as basic provisions for prosecution in norms considered as a hallmark of the codification of Indonesian criminal law. This renewal in the RKUHP leaves crucial issues, one of which is by incorporating elements of law that live in society (The Living Law) and make laws that live in society as the basis for determining whether someone can be convicted or the basis for prosecution. This study uses a normative juridical method with a descriptive analytical approach. The inclusion of the law that lives in society into Article 2 of the RKUHP shows that there has been a conflict with the principle of legality which is the main principle of Indonesian criminal law as stipulated in Article 1 of the RKUHP which has implications for legal certainty